2016
DOI: 10.4110/in.2016.16.6.344
|View full text |Cite
|
Sign up to set email alerts
|

Reference Values for a Panel of Cytokinergic and Regulatory Lymphocyte Subpopulations

Abstract: Lymphocyte subpopulations producing cytokines and exerting regulatory functions represent key immune elements. Given their reciprocal interdependency lymphocyte subpopulations are usually assayed as diagnostic panels, rather than single biomarkers for specialist clinical use. This retrospective analysis on lymphocyte subpopulations, analyzed over the last few years in an outpatient laboratory in Northeast Italy, contributes to the establishment of reference values for several regulatory lymphocytes currently l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 108 publications
2
16
1
Order By: Relevance
“…To the best of our knowledge, only one previous study from Northeast Italy [17] reported the reference ranges of Th1, Th2, Th17, and Treg cells. Obvious differences in the reference values of CD4 + T cell subpopulations were observed between the present study and the published data from Northeast Italy [17], which could be associated with race and sample sizes. Of note, among the primarily identified CD4 + T cell subsets, Th1, Th2, Th17, and Treg cells were associated with different tagging strategies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To the best of our knowledge, only one previous study from Northeast Italy [17] reported the reference ranges of Th1, Th2, Th17, and Treg cells. Obvious differences in the reference values of CD4 + T cell subpopulations were observed between the present study and the published data from Northeast Italy [17], which could be associated with race and sample sizes. Of note, among the primarily identified CD4 + T cell subsets, Th1, Th2, Th17, and Treg cells were associated with different tagging strategies.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, there was only one previous study from Northeast Italy [17] that determined the Fig. 1 Age distribution among all healthy volunteers, males or females.…”
Section: Comparisons Of Reference Ranges With Published Datamentioning
confidence: 99%
See 1 more Smart Citation
“…The frequencies and absolute numbers of B cells were slightly lower in Han Chinese individuals of the Shanxi region than in individuals from Hong Kong, 9 Germany 12 and Singapore. 13 Compared with individuals in Italy, 14 higher percentages and absolute numbers of Treg cells and lower percentages and absolute numbers of Th17 cells were observed in Han Chinese individuals of the Shanxi region.…”
Section: Resultsmentioning
confidence: 98%
“…Because reference intervals for lymphocytes and CD4+ T cell subsets may differ by race, we compared lymphocyte and CD4+ T cell subset reference ranges in diverse racial groups ( Table 4 9 13 and Table 5 14 ). Absolute numbers of CD4+ T cells in Han Chinese individuals of the Shanxi region were lower than those in individuals from Hong Kong, 9 Beijing, 10 Germany 12 and Singapore.…”
Section: Resultsmentioning
confidence: 99%